Primary textbooks and materials for the OECS: A study of affordable and sustainable options - Clare, William (Educom International Inc, 1991)
This study was designed and carried out in consultation with the Organisation of Eastern Caribbean States (OECS) Secretariat, and in collaboration with the Ministries of Education in participating countries. It provides an inventory of curricula, textbooks, and other learning materials in use in the OECS, and assesses suitability for standardization on a regional basis. It also identifies the problems associated with the affordability and availability of texts, and provides an analysis of the various regional textbook publishing initiatives. The study found an impending crisis situation in textbook distribution, and an inefficient and very costly decentralized system that demanded reform in order to ensure affordable and available textbooks. The key recommendations dealt with: 1) a standardized textbook selection process through regional committees, to ensure uniform textbook requirements that allow for economies of scale in purchasing; 2) a textbook rental plan to ensure that valuable textbooks are re-used, provided to all students on an equitable basis, and that the cost of textbooks to parents is brought to manageable and sustainable dimensions; and 3) a regional approach to textbook publishing based on large, economical projects of popular existing textbooks, through the purchase of rights from international and regional publishers
Submitted to the Canadian International Development Agency by Educom International Inc.
Keywords: Organisation of Eastern Caribbean States